On the stance of macroprudential policy - Stephen G. Cecchetti; Javier Suárez (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
In this report we outline how a formulating normative measure of macroprudential policy stance requires a framework containing objectives, tools and transmission mechanisms. To complement the currently prevailing narrative approach, we apply lessons from the monetary policy to macroprudential policy. We begin with by proposing that the ultimate objective of macroprudential policy is to minimise the frequency and severity of economic losses arising from severe financial distress and then integrate the concept of growth-at-risk into the framework. Implementation of our framework for the evaluation of the macroprudential policy stance faces a series of challenges, including availability of the appropriate data, that policymakers generally have multiple objectives and tools, and the uncertain responses of economic agents to macroprudential policy actions.
Keywords: 330; financial market supervision; monetary policy; EU countries; Finanzmarktaufsicht; Geldpolitik; EU-Staaten